Properties of Cattle Viruses, Preserved at Moderately Low Temperatures - Stegniy, M. Yu. (Problems of Cryobiology and Cryomedicine, 2003)
The results of investigations on the study of infectious, antigenic and immunogenic properties of viruses stored under moderately low temperatures are presented. The decrease of infectious activity and immunogenic properties of viruses is found during a long-term storage. Some strains are completely inactivated under these conditions.